Intelligence, Stress and Cognitive Functions Assessment after three months Practice of Moderate Intensity Physical Exercise - Mohita Singh; Sunil Sachdev; Dev Raj (Dr. Annil Mahajan, 2022)
Background: Aerobic exercises produce lasting effect on higher brain functions and promote positive changes in one's mental health, intelligence, cognitive functions like memory, attention and ability to develop better strategies to cope with stressful encounters. Present study was designed to explore the role of three months practice of aerobic exercise on intelligence level, cognitive functions and stress parameters. Material and Method: The study was conducted on 50 subjects for three months duration to assess stress reactivity in subjects with varying level of general intelligence (GI) and emotional intelligence (EI). The effect moderate intensity physical exercise (MIPE) was assessed on GI, EI, stress parameters, cognitive functions and the data obtained was compared with basal values recorded using standard scales. Result: There was significant improvement in IQ and cognitive functions after three months practice of MIPE. Acute stress, chronic stress as well as stress related parameters showed significant improvement post exercise intervention. Conclusion: MIPE improved individual's level of GI, reduced stress parameter values and improved memory and attention concentration span.